STRATEGI PENGEMBANGAN KARIR DALAM MENINGKATKAN KREATIVITAS KERJA PADA STAF PALANG MERAH INDONESIA KOTA BANDA ACEH - Hatta, Kusmawati; Azhari, Azhari; Zubaidah, Zubaidah (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2023)
Abstract: Career development is urgently needed in increasing the resources of the Indonesian Red Cross in Banda Aceh City so that staff are ready when facing a sudden disaster. Therefore, the purpose of this study was to determine the qualifications of Indonesian Red Cross workers, the Indonesian Red Cross Staff Work Program that was applied to the implementation and creativity of employees, and how the stages of career development of Indonesian Red Cross Staff were. In taking the sample, the writer uses purposive sampling technique. Data collection techniques with observation techniques, interviews and documentation. After getting data from the field, the results of the research can be seen that the career development strategy in increasing the creativity of the Indonesian Red Cross staff in Banda Aceh City. First, the qualifications of workers are very diverse and not in accordance with their field of work, so they need data from individuals to adjust their work. Second, having a work program from each field, namely: (a) Searching for blood donor locations in collaboration with partners and granting charters; (b) perform services and data collection and fulfill the facilities and infrastructure; (c) Complete documentation to complete requests from the Food and Drug Administration in the process of complying with Good Manufacturing Practices; (d) Training on logistics and disaster management assessment; (e) Socialization and simulation of public and school health; (f) Proposing permanent employees and refresting data collection. Third, the career development strategy of Indonesian Red Cross staff consists of three strategic processes, namely: (a) scheduled training; (b) internship; (c) seminars and workshops.Keywords: Strategy; Career Development; Work Creativity; PMI Staff.Abstrak: Pengembangan karir sangat dibutuhkan dalam meningkatkan sumber daya Palang Merah Indonesia Kota Banda Aceh sehingga staf siap bertugas saat ada bencana yang melanda tiba-tiba. Oleh karena itu tujuannya dilaksanakan penelitian ini ialah untuk mengetahui kualifikasi para pekerja staf Palang Merah Indonesia, Program kerja Staf Palang Merah Indonesia yang diterapkan untuk pencapaian kinerjanya dan kreativitas kerjanya, serta bagaimana tahapan pengembangan karir Staf di Palang Merah Indonesia. Dalam pengambilan sampel penulis menggunakan teknik purposive sampling. Teknik pengumpulan data dengan teknik observasi, wawancara dan dokumentasi. Setelah mendapatkan data yang diperoleh dari lapangan, maka hasil penelitian dapat diketahui bahwa strategi pengembangan karir dalam meningkatkan kreativitas pada staf Palang Merah Indonesia Kota Banda Aceh. Pertama, kualifikasi para pekerja sangat beragam dan belum sesuai dengan bidang pekerjanya, sehinga membutuhkan data dari perorang untuk menyesuaikan pekerjaanya. Kedua, memiliki program kerja dari masing-masing bidang yaitu: (a) Pencarian lokasi donor darah dengan bekerja sama dengan mitra-mitra dan pemberian piagam; (b) Melakukan pelayanan dan pendataan serta memenuhi perlengkapan sarana dan prasarana; (c) Melengkapi dokumentasi untuk melengkapi permintaan dari Badan Pengawasan Obat dan Makanan dalam proses pemenuhan Good Manufacturing Practices; (d) Pelatihan logistic dan dan manajemen bencana assesmen; (e) Sosialisasi dan simulasi kesehatan ke masyarakat dan sekolah; (f) Pengusulan pegaawai tetap dan refrest pengimputan data. Ketiga, strategi pengengembangan karir staf Palang Merah Indonesia terdapat tiga proses strategi yaitu: (a) pelatihan dengan jadwal schedule; (b) magang; (c) seminar dan workshop.Kata Kunci: Strategi; Pengembangan Karir; Kreativitas Kerja, Staf PMI.